The expert evaluation and informational entropy in reconnaissance data processing - Mammadov, Vugar Mammadhuseyn (Національний технічний університет "Харківський політехнічний інститут", 2019)
The reconnaissance data processing plays muchrole in warfare. The validity of this information is one of the most necessitiesfor staff correct decision - making. Information entropy is a measure of data uncertainty. In information theory the concept of entropy describes how much information there is in signal or event. Information entropy relates to uncertainty amount concerning an event associated with given probability distribution. In this paper, the main importance of information entropy has been shown. In the same time, the application of both information entropy and expert evaluation methods inreconnaissance data processing has been considered. In consideration of the several sources of reconnaissance data, the calculation method of this information validity assessment has been offered on the basis of information entropy and expert evaluation.

Обробка розвідувальної інформації відіграє велику роль у військових діях. Обґрунтованість цієї інформації є найбільш необхідною для вірного прийняття рішення командуванням. Інформаційна ентропія це є міра невизначеності даних. У теорії інформації концепція ентропії описує кількість інформації в сигналі або подію. Інформаційна ентропія встановлює кількісний зв'язок невизначеності, що стосується події, асоційований з даними про розподіл ймовірності. У даній статті показана велика роль інформаційної ентропії. Розглянуто одночасне застосування методів інформаційної ентропії та експертної оцінки в обробці розвідувальних даних. З урахуванням декількох джерел розвідувальної інформації, запропонований метод оцінки правдоподібності цієї інформації на основі інформаційної ентропії та експертної оцінки.
Експертна оцінка та інформаційна ентропія в обробці розвідувальних відомостей
Keywords: reconnaissance data processing; data source; обробка розвідувальної інформації; джерело інформації